1980
DOI: 10.1111/j.1365-2265.1980.tb03136.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Function in the Prader‐willi Syndrome

Abstract: Hypothalamic, pituitary and gonadal function was studied in five male and three female patients with the Prader-Willi syndrome. All were clinically hypogonadal: all males had low circulating testosterone levels, although in two females basal plasma oestradiol was within the normal range for the early follicular phase of the menstrual cycle. Basal gonadotrophin levels were low and the response to the intravenous ater 10 days and 6 weeks treatment with oral clomiphene (200 mg daily) was followed by a normal rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Hypogonadotropic hypogonadism was found in more than 25% of the participants in our study, while in males with PWS, severe gonadotropin deficiency is a rare cause of hypogonadism (6,(8)(9)(10). The dissimilarity in hypothalamic-pituitary function between males and females with PWS might be explained by the divergence in the regulation of FSH secretion between normal males and females.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Hypogonadotropic hypogonadism was found in more than 25% of the participants in our study, while in males with PWS, severe gonadotropin deficiency is a rare cause of hypogonadism (6,(8)(9)(10). The dissimilarity in hypothalamic-pituitary function between males and females with PWS might be explained by the divergence in the regulation of FSH secretion between normal males and females.…”
Section: Discussionmentioning
confidence: 64%
“…Clinical features, attributed mainly to hypothalamic dysfunction (2, 5-7), include severe hypotonia and feeding difficulties in infancy, an insatiable appetite leading to severe obesity in childhood, short stature, and hypogonadism as well as dysmorphic features and variable degrees of mental retardation (2)(3)(4). Although hypogonadism has often been attributed to hypothalamic dysfunction, some studies show that a primary testicular defect contributes to the hypogonadism in PWS males (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, experimental hyperghrelinemia in prepubertal male rats decreased serum LH and testosterone concentration and delayed timing of puberty [64]. Moreover, an overexpression of ghrelin gene resulting in high level of ghrelin was reported for Willi-Prader syndrome with combined impairment of LH secretion, LH stimulated testosterone production and local, presumably, primary defects in Sertoli and gametogenic cell line maturation [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic dysfunction, as already originally presumed by Prader et al, appears to underlie many of the features of PWS, including hypogonadism [10, 11], abnormal appetite control, high pain threshold and sleep disorders, but no overt structural abnormalities of the hypothalamus have been found yet. In recent years, it was shown that growth hormone (GH) deficiency due to hypothalamic dysregulation contributes not only to the abnormal growth pattern and osteopenia, but also to the excess of body fat and to the deficit of lean body mass, with consequently reduced energy expenditure.…”
Section: Introductionmentioning
confidence: 99%